SOSIALISASI PEMILAHAN SAMPAH ORGANIK DAN ANORGANIK DI BANJAR MUKTI, DESA SINGAPADU - Ni Kadek Rini Purwati; Ni Luh Putu Cahayani; Sumetri Susana Uwa; I Wayan Agus Rama; Angelius Viteriski Janggur; I Kadek Aditya Pramana; I Komang Agusnarayana; I Gede Suta Wiweka (ASOSIASI IDEBAHASA KEPRI, 2026)
Waste problems have become one of the increasing environmental challenges, especially in densely populated residential areas. The lack of public awareness in sorting organic and inorganic waste causes environmental pollution and decreases public health quality. The socialization activity on sorting organic and inorganic waste in Banjar Mukti, Singapadu Village aims to increase public knowledge, understanding, and awareness regarding the importance of waste management starting from households. This activity was conducted in February 2026 and was attended by approximately 10 participants consisting of PKK mothers and heads of households in Banjar Mukti. The methods used in this activity included observation, counseling, discussion, waste sorting demonstrations, and direct practice with the community. The results of the activity showed that the community began to understand the differences between organic and inorganic waste and the importance of maintaining environmental cleanliness. This socialization also had a positive impact on changing community behavior in disposing of and sorting waste according to its type. Through this activity, it is hoped that the people of Banjar Mukti can implement proper and sustainable waste management in order to create a clean, healthy, and comfortable environment.